New records of Reduviidae (Hemiptera: Heteroptera) from Colombia and other Neotropical countries - Forero, Dimitri (Zootaxa, 2006)
One subfamily, 27 genera, and 48 species of Reduviidae are recorded for the first time from Colombia and other Neotropical countries. Comments on those taxa, and new localities and notes for other previously known species, are given. For the first time, the female of Opisthacidius picturatus is described and its pronotum figured. Morphological details on Orbella lugubris, Pessoaia limai, Phasmatocoris spectrum, and Pothea annulipes are provided.